Combining Rapid Data Independent Acquisition and CRISPR Gene Deletion for Studying Potential Protein Functions: A Case of HMGN1 - Mehnert, Martin; Li, Wenxue; Wu, Chongde; Salovska, Barbora; Liu, Yansheng (Proteomics, 2019)
CRISPR-Cas gene editing holds substantial promise in many biomedical disciplines and basic research. Due to the important functional implications of non-histone chromosomal protein HMG-14 (HMGN1) in regulating chromatin structure and tumor immunity, gene knockout of HMGN1 is performed by CRISPR in cancer cells and the following proteomic regulation events are studied. In particular, DIA mass spectrometry (DIA-MS) is utilized, and more than 6200 proteins (protein- FDR 1%) and more than 82 000 peptide precursors are reproducibly measured in the single MS shots of 2 h. HMGN1 protein deletion is confidently verified by DIA-MS in all of the clone- and dish- replicates following CRISPR. Statistical analysis reveals 147 proteins change their expressions significantly after HMGN1 knockout. Functional annotation and enrichment analysis indicate the deletion of HMGN1 induces histone inactivation, various stress pathways, remodeling of extracellular proteomes, cell proliferation, as well as immune regulation processes such as complement and coagulation cascade and interferon alpha/ gamma response in cancer cells. These results shed new lights on the cellular functions of HMGN1. It is suggested that DIA-MS can be reliably used as a rapid, robust, and cost-effective proteomic-screening tool to assess the outcome of the CRISPR experiments.
Keywords: CRISPR-Cas Systems; nádorové buněčné linie; HMGN1 Protein; proteomika; editace genu; Gene Deletion; CRISPR-Cas9; CRISPR-Cas systémy; HeLa Cells; Chromatin; Cell Proliferation; protein HMGN1; Cell Line, Tumor; Gene Editing; HMGN1; clone effect; protein function; gene deletion; delece genu; Proteomics; Humans; data independent acquisition; proliferace buněk; chromatin; HeLa buňky; lidé